2018
DOI: 10.1177/0954409718777374
|View full text |Cite
|
Sign up to set email alerts
|

Robust active guidance control using the µ-synthesis method for a tramcar with independently rotating wheelsets

Abstract: This paper presents a robust active guidance controller that uses the µ-synthesis method to improve the ability of guidance and to reduce the wheel–rail wear under the consideration of system nonlinearity, parameter uncertainty, and measurement noise in tramcars with independently rotating wheelsets (IRWs). Each wheel of the tramcar is connected to a sider motor, and the active yaw moment is generated by the torque differences between the left and right wheels in the same axle. To achieve local control, the wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…A robust control approach was successfully applied on a 1:5 test rig by Lu et al [142]. The scaled vehicle runs on a real track with reduced gauge differently from most of the applications that involve tests on experimental IRW vehicles.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A robust control approach was successfully applied on a 1:5 test rig by Lu et al [142]. The scaled vehicle runs on a real track with reduced gauge differently from most of the applications that involve tests on experimental IRW vehicles.…”
Section: Methodsmentioning
confidence: 99%
“…These are then used to provide traction, wheel guidance and stability control. The motors can be externally mounted and connected to the wheelset through a gearbox (Pérez et al [137], Liang et al [139,140], Ahn et al [141], Lu et al [142] and Farhat et al [98,143]) as shown in Fig. 30 or embedded inside the wheels (Mei et al [144], Ji et al [145] and in the 'Next Generation Train' project in [124], [146][147][148][149]).…”
Section: (B) Driven Independently Rotating Wheel (Dirw)mentioning
confidence: 99%
See 2 more Smart Citations
“…A study on the assessment stability and active guidance of railway vehicles was conducted by Goodall and Powell [16], [17]. Lu et al studied a robust active controller to handle the uncertainty and nonlinear characteristics [18].…”
Section: Introductionmentioning
confidence: 99%